Is anatomy of the posterolateral corner always the same? - Sun, Luning; Lin, Darius E.; Zhao, Jinzhong (Annals of Joint, 2019)
Multiple ligament injuries of the knee usually occur after high-velocity trauma, with the posterolateral corner (PLC) being the most commonly injured. It has been estimated that 60% of patients with posterior cruciate ligament (PCL) injuries also have a concomitant injury to one or more of the posterolateral structures (1-4).